2017
DOI: 10.1016/j.clinimag.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antiangiogenic therapy combined with Transarterial Chemoembolization on enhancement based quantitative tumor response assessment in patients with hepatocellular carcinoma

Abstract: Purpose To investigate whether Bevacizumab compromises early response assessment after Transarterial Chemoembolization (TACE) in patients with hepatocellular carcinoma by 3D quantitative European Association for the Study of the Liver (qEASL) criteria in comparison to other imaging-based criteria. Materials and Methods Each of 14 patients receiving TACE and bevacizumab was matched with two patients receiving TACE alone. Baseline and Follow-up MRI was retrospectively analyzed regarding qEASL and other imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Starting from promising preclinical evidence, 28,29 several trials focusing on the combination of TACE and TKIs have been conducted with heterogeneous results 30–36 . Interestingly, the results from the phase III multicenter randomized controlled combination LAUNCH trial have recently been presented at ASCO 2022, thus highlighting a survival benefit from TACE plus lenvatinib when compared with lenvatinib alone in a cohort of patients affected by advanced HCC with good liver function (mOS 17.8 vs. 11.5 months) 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from promising preclinical evidence, 28,29 several trials focusing on the combination of TACE and TKIs have been conducted with heterogeneous results 30–36 . Interestingly, the results from the phase III multicenter randomized controlled combination LAUNCH trial have recently been presented at ASCO 2022, thus highlighting a survival benefit from TACE plus lenvatinib when compared with lenvatinib alone in a cohort of patients affected by advanced HCC with good liver function (mOS 17.8 vs. 11.5 months) 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Starting from promising preclinical evidence, 28,29 several trials focusing on the combination of TACE and TKIs have been conducted…”
Section: Discussionmentioning
confidence: 99%
“…48 In a study comparing TACE + bevacizumab to TACE alone, Smolka et al reported that bevacizumab did not impede response to TACE assessed by the quantitative EASL system for evaluation of local response (qEASL). 49 Given the hypothetical risk of anti-angiogenic drugs altering the tumour vasculature, which may impact negatively on the delivery of TACE this is reassuring, while the combination of TACE with anti-angiogenic drugs has been disappointing in terms of survival outcomes, there are encouraging data for the combination of bevacizumab with the T cell checkpoint inhibitor, atezolizumab (and indeed for other CPIs in combination with VEGFR tyrosine kinase inhibitors, e.g. lenvatinib with pembrolizumab) and such drug combinations may be tested in combination with TACE in future trials.…”
Section: Combination Of Intra-arterial Therapy + Sorafenibmentioning
confidence: 99%
“…lenvatinib with pembrolizumab) and such drug combinations may be tested in combination with TACE in future trials. 49 Given the potential safety signals, scheduling of bevacizumab in relation to TACE requires caution.…”
Section: Combination Of Intra-arterial Therapy + Sorafenibmentioning
confidence: 99%